2015
DOI: 10.1371/journal.pone.0128468
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Effects Induced in Mytilus galloprovincialis Treated with Oxytetracycline at Different Temperatures

Abstract: The present study evaluatedthe interactive effects of temperature (16°C and 24°C) and a 4-day treatment with the antibiotic oxytetracycline (OTC) at 1 and 100μg/L on cellular and molecular parameters in the mussel Mytilus galloprovincialis. Lysosomal membrane stability (LMS), a sensitive biomarker of impaired health status in this organism, was assessed in the digestive glands. In addition, oxidative stress markers and the expression of mRNAs encoding proteins involved in antioxidant defense (catalase (cat) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Indeed, our data confirm and support the use of this fluorochrome for efficiently evaluating lipid peroxidation, as we easily measured more lipid peroxidation at the beginning of the heat‐stress period, followed by a return to control‐group levels at a later time. This profile also implicates an active compensatory mechanism in the mussel, perhaps involving the production of antioxidants that are capable of recovering the oxidative status of lipids to within a physiological range (Frenzilli et al, ; Banni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our data confirm and support the use of this fluorochrome for efficiently evaluating lipid peroxidation, as we easily measured more lipid peroxidation at the beginning of the heat‐stress period, followed by a return to control‐group levels at a later time. This profile also implicates an active compensatory mechanism in the mussel, perhaps involving the production of antioxidants that are capable of recovering the oxidative status of lipids to within a physiological range (Frenzilli et al, ; Banni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The relative importance of pharmaceuticals among other environmental pollutants cannot be stated at the moment; however, pharmaceuticals can induce profound biological effects and thus may act as additional stressors on marine ecosystems already impacted by other factors. Modifications of pH and temperature associated with climate change influence the chemical properties of most pharmaceuticals, which therefore may contribute differently to the global effect . Furthermore, the impact of pharmaceuticals on coastal environments is expected to increase with the increasing number of inhabitants in such areas and the increasing pressures attributable to human activities such as aquaculture , posing relevant implications for marine risk assessment and the determination of potential consequences for ecological and human health that cannot be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Nakano et al (2018) found a reduction in HSP70 (stress protein) when fish Coho salmon was exposed to oxytetracycline. Furthermore, Banni et al (2015) found that oxytetracycline causes a drastic down-regulation of mRNA encoding hsp 27 protein. Similar studies by Franzellitti and Fabbri (2013) suggested that the impairment of regulatory pathways triggered by low concentrations of pharmaceuticals may affect the ability of animals to elaborate defense strategies or adapt to stress 2+ factors.…”
Section: Resultsmentioning
confidence: 99%
“…The other probable reason may be the formation of lipoproteins which are utilized to repair the damaged cell. Oxytetracycline decreased the lysosomal membrane stability in mussels (Banni et al, 2015) and enhance protein catabolism (Viarengo et al, 2007).…”
Section: O N L I N E C O P Y J Thakur Et Al: Oxytetracycline Induced ...mentioning
confidence: 99%